Comparative antihemolytic and radical scavenging activities of strawberry tree (Arbutus unedo L.) leaf and fruit - Mendes, Lídia (2021)
The present study reports the antioxidant properties of Arbutus unedo L. leaf and fruit extracts using different in vitro assays including (i) reducing power, (ii) scavenging effect on DPPH free radicals, and (iii) inhibitory effect on AAPH-induced hemolysis and lipid peroxidation in human erythrocytes. All assays demonstrated antioxidant efficiency for A. unedo L. aqueous extracts, being consistently higher in the leaf. EC(50) values for reducing power and DPPH radical scavenging activities were, respectively, 0.318 ± 0.007 and 0.087 ± 0.007 mg/mL for leaf, and 2.894 ± 0.049 and 0.790 ± 0.016 mg/mL for fruit extracts. Under the oxidative action of AAPH, A. unedo leaf and fruit extracts protected the erythrocyte membrane from hemolysis (IC(50) of 0.062 ± 0.002 and 0.430 ± 0.091 mg/mL, respectively) and decreased the levels of malondialdehyde, a breakdown product of lipid peroxidation (IC(50) of 0.075 ± 0.014 and 0.732 ± 0.452 mg/mL, respectively). In accordance with antioxidant activity, phenolic content was found to be significantly higher in leaf extract. To our knowledge, this is the first time that the antioxidant activity of A. unedo species is evaluated using human biological membranes. Overall, our results suggest that A. unedo leaves are a promising source of natural antioxidants with potential application in diseases mediated by free radicals.